Music and Modernity among First Peoples of North America - Levine, Victoria Lindsay, 1954-; Robinson, Dylan (Music/culture., 2018)
Indigenous and settler scholars from both Canada and the United States explore topics that range from powwow, Native Classical, and hip-hop to television soundtracks and experimental music. Working from the premise that multiple modernities exist for Indigenous peoples, the authors seek to understand contemporary musical expression from Native perspectives and to decolonize the study of Native American/First Nations music -- Provided by publisher.